Association between serum uric acid levels and white matter hyperintensities in patients with mild ischemic stroke - Chaoxin Chai; Chaoxin Chai; Chaoxin Chai; Yuqi Cui; Yuqi Cui; Yuqi Cui; Meng Li; Meng Li; Meng Li; Jianing Xia; Jianing Xia; Jianing Xia; et al. (Frontiers in Neurology, 2025)
ObjectiveThis study aims to investigate the association between uric acid (SUA) level and white matter hyperintensities (WMH) in patients with mild ischemic stroke.Methods and resultsThis study retrospectively analyzed 290 patients with mild ischemic Stroke who were hospitalized at the Second Hospital of Hebei Medical University from March 2021 to January 2022. General clinical information and laboratory test results were collected. WMH was interpreted on MRI, and periventricular hyperintensity (PVH) and deep white matter hyperintensities (DWMH) were scored, respectively. According to the score of Fazekas, WMH was divided into two groups. Factors influencing WMH severity were analyzed, and the relationship between SUA and WMH was further explored. The results showed that the SUA of patients with moderate to severe DWMH was higher than that of patients with no or mild DWMH (345.10 ± 97.52 μmol/L vs. 317.99 ± 91.21 μmol/L, p = 0.028). There was no significant difference in SUA between the moderate to severe PVH group and the no or mild PVH group (336.49 ± 99.29 μmol/L vs. 319.16 ± 89.92 μmol/L, p = 0.131). Spearman correlation analysis showed that SUA was positively correlated with the severity of DWMH (r = 0.123, p = 0.037), while SUA was not significantly correlated with PVH severity (r = 0.070, p = 0.234). After adjusting for confounders by multifactor logistic regression, SUA was independently correlated with DWMH severity (OR: 1.005, 95% CI: 1.002–1.009, p = 0.004). There was no significant correlation between SUA and PVH (OR: 1.003, 95% CI: 1.000–1.006, p = 0.051).ConclusionSUA is an independent risk factor for DWMH in patients, and there is no significant correlation between SUA level and PVH.